Are functional traits a good predictor of global change impacts on tree species abundance dynamics in a subtropical forest?. (27th August 2015) - Li, Ronghua; Zhu, Shidan; Chen, Han Y. H.; John, Robert; Zhou, Guoyi; Zhang, Deqiang; Zhang, Qianmei; Ye, Qing; He, Fangliang
Abstract Significant changes in the composition of tree species have been observed in various forests worldwide. We hypothesised that these changes might result from variable sensitivities of species to global change, and species sensitivities might be quantified, using functional traits. Employing long‐term (1978–2010) species abundance data of 48 tree species from a permanent subtropical forest plot, where multiple global change factors have been observed, including soil drying, we examined the relationships between temporal trends in abundance and suits of functional traits. We found that species with high photosynthesis rates, leaf phosphorus and nitrogen concentrations, specific leaf area, hydraulic conductivity, turgor loss point and predawn leaf water potential had increased in abundance, while species with opposite trait patterns had decreased. Our results demonstrate that functional traits underlie tree species abundance dynamics in response to drought stress, thus linking traits to compositional shifts in this subtropical forest under global changes.